Methanol and Formic Acid Activation Over Dispersed Metals (Pd, Pt, Au, Cu) on Ceria. - Yi, Nan. (2017)
Abstract: Clean and efficient hydrogen production is of interest because of the potential of hydrogen to be the energy carrier of the future. Production of hydrogen from water-splitting is the long-term goal as it would be a clean and sustainable technology, once enough progress has been made to reduce the associated cost. For the short-term, hydrogen can be derived from renewable biomass or biomass plus fossil (or waste) fuel mixtures, in ways that minimize the carbon footprint of the process. In order to harness chemical energy into a practical and usable form, catalytic processes that efficiently extract the hydrogen are required. For these applications, new type catalysts containing only trace amounts of expensive noble metals are under intense investigation. In this thesis, highly dispersed metals as sub-nm clusters and cations on cerium oxide support have been prepared, characterized, and evaluated for the production of hydrogen by methanol steam reforming. An earth-abundant oxide, silica, has also been considered as support for alkali-promoted Pt, a new catalyst for the decomposition of formic acid to hydrogen and carbon dioxide. The first part of my thesis demonstrates how a small amount (<1 wt%) gold on nanoscale ceria, is a novel, highly active catalyst for the steam reforming of methanol and the decomposition of formic acid. For these studies, a mixture of vapor-phase methanol and water, at a molar ratio of 1:1.3 was used, with the amount of water vapor typically not exceeding 3 %, the saturation vapor pressure of water at ambient conditions. Dispersion of the gold in ceria is crucial for activity. A shape effect of ceria on the catalytic activity of gold was identified by using single crystals of ceria prepared at the nanoscale as nanorods, nanocubes, and nanopolyhedra. Gold was found to disperse atomically on the {110} surfaces of the nanorods, but not at all well on the {100} surfaces of the ceria nanocubes, where it formed nanoparticles, ~ 3 nm in size. Consequently, the activity of the latter was negligible while the gold dispersed on the {110} surfaces of ceria was a high-activity catalyst, converting methanol to H2 and CO2 at temperatures below 250 oC. The Aun-O-Ce catalyst sites are active also for the water-gas shift reaction. However, in the presence of methanol they preferentially adsorb methanol over carbon monoxide; hence they catalyze the reactions of the former selectively. The apparent activation energies and the turnover rates on the gold-ceria catalysts were the same irrespective of the shape of ceria; i.e. the shape effect is indirect, controlling simply the number of active Au-Ox active sites on each surface of ceria. Cerium oxide is an excellent dispersant for all metals, which it stabilizes in cationic surface oxygen species over its oxygen defects. It thus allows to compare the different M-Ox catalytic properties for various reactions, especially for oxidation reactions of interest in the production of hydrogen. By using ceria nanorods, which have a large number of oxygen vacancies on their {110} surfaces, it was possible to disperse and evaluate different metals as M-Ox catalytic sites for the steam reforming of methanol. Different reaction pathways over the Group VIII (Pd, Pt) and Group IB (Cu, Au) metal sites on ceria were identified. As a screening tool, temperature -programmed reactions under dynamic heating, as well as isothermal kinetics testing in microreactor were used. Group IB metals (Cu, Au) catalyzed the methanol coupling reactions to produce methyl formate. In the presence of water, methyl formate is hydrolyzed into formic acid, and finally H2 and CO2 are produced by the decomposition of formic acid on the gold species. This pathway explains gold-ceria displayed excellent CO2 selectivity in steam reforming of methanol. The water-gas shift reaction equilibrium does not limit this pathway; hence the selectivity to H2 is maximal. On the other hand, decomposition of methanol followed by the water gas shift reaction is the sole pathway for Group VIII metals (Pd and Pt) on ceria. In separate studies of the formic acid decomposition, the dehydrogenation pathway was established to derive from the presence of the gold species. On gold-free ceria, the dehydration pathway is followed. Stability tests under shut-down/start-up cyclic operation showed the Au-CeOx to be stable. Their resistance to water and carbon monoxide poisoning opens the way for application of gold-ceria as electrocatalyst component to direct formic acid fuel cells. The second part of my thesis focused on understanding the mechanisms of sodium- modified platinum species for methanol and formic acid reactions. The formation of Na-Pt-Ox(OH) ensembles active for the low-temperature water-gas shift reaction was shown in recent work from our lab. Activity of these species was found even on silica supports, on which Na-free Pt is inactive. In this thesis the same materials were investigated as catalysts for methanol and formic acid reactions. Activity for these reactions was indeed promoted and hydrogen was produced at ambient temperatures. The reaction pathway over the Na-promoted Pt on silica was the same as that of Pt-CeOx. However, the atomic dispersion of Pt-O species by the Na addition, allows the use of an earth-abundant support, i.e. silica, and the use of much less platinum for the same activity. These catalysts are then to be preferred as they make better use of valuable resources and are good candidates for sustainable hydrogen and energy production applications. In summary, the findings of this thesis demonstrate that through the choice of suitable supports and promoters as ligands, noble metal catalysts can be prepared in atomic dispersions with high activity and stability for the reactions of interest to fuel processing to produce hydrogen, which also minimize their associated cost. As a concluding remark, potentially these findings are general, and it is recommended that they be explored also for base metal oxide catalysts in future work.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisors: Maria Flytzani-Stephanopoulos, and Howard Saltsburg.; Committee: Robert Weber, Terry Haas, and Hyunmin Yi.; Keyword: Chemical engineering.